2018
DOI: 10.1002/eat.22845
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the brief loss of control over eating scale (LOCES‐B) in early adolescents

Abstract: Findings suggested that the LOCES-B is a reliable and valid measure of LOC eating in early adolescents. The availability of the LOCES-B has the potential to elucidate the developmental trajectories, predictors, and outcomes of LOC eating across the full severity spectrum in large cohort studies of youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…In contrast to the ELOC, the LOCES‐brief demonstrated full MI between men and women, which replicates and extends prior research conducted in community adolescents (Vannucci & Ohannessian, ). Current findings suggest that the LOCES‐brief performs similarly in male and female college students.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In contrast to the ELOC, the LOCES‐brief demonstrated full MI between men and women, which replicates and extends prior research conducted in community adolescents (Vannucci & Ohannessian, ). Current findings suggest that the LOCES‐brief performs similarly in male and female college students.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, the 7‐item version provided excellent fit to the data in both samples. For parsimony and consistency with prior research (Vannucci & Ohannessian, ), the LOCES‐brief was examined in subsequent analyses. Factor loadings were high ( r = .47–.81), and internal consistencies were good ( α s = .91–.94) across samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to including information from other important socializing agents, other types of eating behaviors could be considered as well. For instance, examining more disruptive eating behaviors, such as food addiction and loss of control while eating, could be of high relevance in adolescence [54][55][56]. Another limitation of this study is its cross-sectional design, which limits us from drawing conclusions about the direction and causality of the associations found.…”
Section: Discussionmentioning
confidence: 95%
“…Of note, previous studies have suggested that subjective binge episodes are clinically meaningful, but have low reliability [ 25 27 ]. Improved diagnostic guidelines, assessment tool instructions, and new measures (e.g., the Eating Loss of Control Scale and the Loss of Control over Eating Scale) may help increase reliability and improve diagnosis and severity assessment across disorders characterized by binge eating [ 10 , 11 , 28 , 29 ]. Our findings could help inform the refinement of these assessment tools to measure LOC.…”
Section: Discussionmentioning
confidence: 99%